The Organotin Spectroscopic Studies of Hydroxamic as a Ligand: A Systematic Review - M. Graisa, Abdualbasit; A. Husain, Amani; Al-Ani, Ahmed; S. Ahmed, Dina; H. Al-Mashhadani, Mohammed; Yousif, Emad (Al-Nahrain Journal of Science, 2022)
This review highlighted the analysis techniques of hydroxamic acid (HAs) and Organotin (IV) Hydroxamates. Different isomerism, keto and enol form, as well as, intra and inter hydrogen bonding are confirmed through spectroscopic studies. In addition all organotin (IV) complexes geometries were studied and explained in this review depending on different analysis techniques done by researchers. Our study is not unique but it gives your attention to be more concern if you will deal with these types of compounds regarding to the functional groups, isomerism, structural information and its geometry.